PENGEMBANGAN WORDWALL (LABIRIN) SEBAGAI EVALUASI PEMBELAJARAN AKIDAH AKHLAK PADA MATERI SIFAT SIFAT ALLAH KELAS VII MTS MUSLIMAT NU PALANGKA RAYA - Abdul Aziz; Noor Haliza; Marlina Wahyu Agustin; Arif Miftahul Khairul Anam; Siprianus Jerawut (CV. ADIBA AISHA AMIRA, 2024)
The use of wordwalls in schools as an interactive learning tool to create various types of educational activities, including games, quizzes and exercises. This research aims to develop and increase the effectiveness of wordwall as a tool for evaluating moral belief learning in class VII D at Mts Muslimat NU Palangka Raya. The problem identified is the lack of use of media in learning moral beliefs, which can hinder students' interest in learning about the material that has been presented by the teacher. The method used is the Research and Development approach (R&D), and the model used is ADDIE which includes needs analysis, selecting games, content development, and classroom trials. Through this process, games are selected with interesting challenge and quiz elements, allows students to learn actively. The results of this research state that on average students feel this media is effective and helps them understand the questions better. Labyrinth media not only increases students' interest in learning, but is also able to create a more enjoyable and meaningful learning experience.